Positive Association Between Fluoroquinolone Exposure and Tendon Disorders: A Nationwide Population-Based Cohort Study in Taiwan - Chang, Chun-Kai; Chien, Wu-Chien; Hsu, Wan-Fu; Chiao, Hao-Yu; Chung, Chi-Hsiang; Tzeng, Yuan-Sheng; Huang, Shao-Wei; Ou, Kuang-Ling; Wang, Chih-Chien; Chen, Shyi-Jou; Wang, Der-Shiun (Frontiers in Pharmacology, 2022)
Introduction Fluoroquinolone exposure is reportedly associated with a higher risk of tendon disorders, tendonitis, or tendon rupture. However, studies in East Asian populations have not confirmed these risks in patients with comorbidities or concomitant medication use. This cohort study was designed to investigate the associations among fluoroquinolone exposure, comorbidities, medication use, and tendon disorders in Taiwan. Materials and Methods This population-based, nationwide, observational, cohort study used data from the National Health Insurance Research Database in Taiwan, a nationwide claims database that covers more than 99% of the Taiwanese population. The study period was from January 2000 to December 2015, and the median follow-up time was 11.05±10.91 years. Patients who were exposed to fluoroquinolones for more than three consecutive days were enrolled, and patients without fluoroquinolone exposure who were matched by age, sex, and index year were enrolled as controls. The associations of comorbidities and concomitant medication use with tendon disorder occurrence were analyzed using Cox regression models. Results The incidence of tendon disorders were 6.61 and 3.34 per 105 person-years in patients with and without fluoroquinolone exposure, respectively (adjusted hazard ratio, 1.423; 95% confidence interval: [1.02,1.87]; p=0.021). Sensitivity analyses yielded similar results. Patients under 18 and over 60 years with fluoroquinolone exposure; those with chronic kidney disease, diabetes, rheumatologic disease, cardiac disease, lipid disorder, or obesity; and those who concomitantly used statins, aromatase inhibitors, or glucocorticoids, had a significantly higher risk of tendon disorders. Conclusion The long-term risk of tendon disorders was higher in patients with fluoroquinolone exposure than in those without fluoroquinolone exposure. Clinicians should assess the benefits and risks of fluoroquinolone use in patients at high risk of tendon disorders who require fluoroquinolone administration.